PERILAKU MENCONTEK SEBAGAI INDIKASI GAGALNYA EFIKASI DIRI (SELF EFFICACY) ANAK DALAM PEMBELAJARAN - Muhammad Nizaar (Universitas Sarjanawiyata Tamansiswa, 2017)
Cheating seems as an ordinary habit for most of teacher, so they tend to ignore it and rarely to discuss as a central issues in learning evaluation. Cheating is one of manifestations in using illegitimate ways, means to achieve a legitimate end. Cheating problems is become very crucial cases since it will be bring into the job places and daily life. Therefore, self-efficacy is absolutely needed to build up the children’s confidence; it is also very important because selfefficacy have many functions, such as: (1) to develop the strong commitment, (2) to establish children in having their grand plans to achieve the goals, (3) to stimulate children’s braveness in facing the challenges, tasks, and tests, and (4) to avoid children from doing any acts which may appear the failure. In order to discover those problems, we need to use the psychological approach based on Albert Bandura’s theory and to invest the religious characters’ values related to the Al-Qur’an in Ali Imran, verse 139. There are two kinds of cheating done by children, they are; (a) cheating by self-effort, in a small note form, in pencil box, tucked inside of calculator, and putting into HP, (b) cheating together, by creating the codes or signs which make them easy to understand each other. The cheating happened not only because of the supervisor’s irresponsible and careless, but also arises from pressures which force children to gain the good score and pass the exam. This habit is supported by the social media and much of link which provide safely cheating tricks, through Facebook, limakaki.wordpress.com, munsypedia.com, caranyontek.blogspot.com, tololpedia.com, etc. Based on the writer analysis, there are two kinds of learning activities which may threat the children’s selfefficacy, are: (1) teacher often gives punishments that make children shame. In fact, punishment itself would arise the negative legitimating among children. It is better to use the Sinaas Apple punishments are termed by Jan Ligthart, (2) teacher less give the students’ opportunity to be more creative. It’s because the class tends to apply the teacher-center learning, where teacher as a central who won’t to be bothered by the questions or student’s feedback. Consequently, we need to change the teacher’s mindset, parents’ views, and also social environment that proved by the result of this study.